2017
DOI: 10.1016/j.chest.2017.04.174
|View full text |Cite
|
Sign up to set email alerts
|

Reduced COPD Exacerbation Risk Correlates With Improved FEV 1

Abstract: A significant correlation between increased FEV and lower COPD exacerbation risk suggests that airway patency is an important mechanism responsible for this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
6
21
0
1
Order By: Relevance
“…In agreement with previous observations, our results establish an inverse correlation between FEV 1 and COPD exacerbation in overlap syndrome similar to COPD‐only patients. Such results can be linked to the higher expression of inflammatory cytokines and frequent colonization of aggressive bacteria in patients with severe pulmonary impairment .…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous observations, our results establish an inverse correlation between FEV 1 and COPD exacerbation in overlap syndrome similar to COPD‐only patients. Such results can be linked to the higher expression of inflammatory cytokines and frequent colonization of aggressive bacteria in patients with severe pulmonary impairment .…”
Section: Discussionsupporting
confidence: 93%
“…And 20% of these patients were hospitalized within the next year due to exacerbation. These findings confirm the previous studies which showed that exacerbation risk correlates with FEV 1 …”
Section: Discussionsupporting
confidence: 92%
“…These findings confirm the previous studies which showed that exacerbation risk correlates with FEV 1 . 3,[5][6][7][8] Comparison of GOLD 2011 with GOLD 2017 in terms of, future risk of moderate and severe exacerbations revealed that, in 2017 revision, groups A and B had higher rates of both moderate and severe exacerbation in the following year. GOLD 2017 groups A and B had 1.5 fold high risk of future moderate exacerbation compared to GOLD 2011 A and B.…”
Section: Discussionmentioning
confidence: 99%
“…[24]. По данным обзора [25] установлено, что каждые 100 мл разницы в увеличении конечного ОФВ 1 между группами терапии сопровождаются уменьшением риска среднетяжелых / тяжелых обострений на 21 % (р < 0,001), а каждые 50 мл -на 11 % (р < 0,001). В данном исследовании обе комбинации приводили к приросту конечного ОФВ 1 > 100 мл.…”
Section: сравнение комбинированных бронходилататоров: данные рандомизunclassified